INFEKSI PADA PENDERITA LUPUS ERITEMATOSUS SISTEMIK: SEBUAH TINJAUAN LITERATUR - Isra Alfisyahri Gunawan (Jurnal Medika Hutama, 2026)
Patients with SLE are highly susceptible to infections, varying from bacterial and viral infections to opportunistic infections with normal or abnormal symptoms. To date, infection is one of the main causes of morbidity and mortality in SLE patients. Objective: to determine the types of infections and pathogens that often invade SLE patients while discussing infection risk factors and infection prevention strategies in SLE patients. Methods: literature search using Publish or Perish, PubMed, Google Scholar, Research Gate, ScienceDirect, and Springer Link databases. The keywords used were “infection” AND “Systemic Lupus Erythematosus”. Results: A total of 1,064 SLE patients with infection were reported in all included studies. Respiratory tract infection was the most common type of infection. Bacteria were the main pathogens of infections reported in all studies. Herpes Zoster was the most common viral infectious disease in all studies. Conclusions: Infection remains a serious complication in SLE patients. Optimizing therapy, vaccination, and infection screening can reduce the risk of infection.